Multi-criteria decision-making methods for the evaluating of a real green supply chain in companies with fast-moving consumer goods. Issue 3 (3rd July 2022) - Rastpour, Elham; Kayvanfar, Vahid; Rafiee, Majid
ABSTRACT: This research aims at determining the main criteria of the green supply chain management (GSCM) and providing a framework to assess and compare the greenness of dairy industries. There has been a research gap in evaluating the greenness of this industry in Iran to be bridged. In the first phase, through studying literature and acquiring academics and experts' opinions, the framework is classified into 8 criteria and 32 sub-criteria as enablers and relevant to the GSCM, considered as base subjects in preparing questionnaires. The second phase uses experts' opinions and through the Fuzzy Delphi method, 26 sub-criteria are screened, confirmed, and employed. Also, the cause-and-effect criteria and sub-criteria (C&SC) are identified by the Fuzzy DEMATEL method. In this context, the fuzzy best-worst multi-criteria decision-making method (FBWM) indicates the most and least important C&SC. Then, by using a Weighted Aggregated Sum Product Assessment Method (WASPAS), the considered companies are evaluated and ranked in terms of greenness, followed by some analyses over the results of real case studies. Ultimately, some managerial insights are extracted, which are fundamental for being regarded green and play the central role in making the companies much more functional with lots of amazing and needful results for them..